Proses Pengambilan Keputusan Konsumen Terhadap Pembelian Fillet Ikan di Kota Pekanbaru - S, Selvia Magdalena; Arief, Hazmi; Yolandika, Clara (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2025)
This study aims to analyze the consumer decision-making process regarding the purchase of fish fillets in Pekanbaru City. The research employed a survey method with a quantitative approach using accidental sampling, involving 110 respondents55 consumers who purchased fish fillets and 55 who did not. Data were analyzed descriptively through five stages of the consumer decision-making process: problem recognition, information search, alternative evaluation, purchase decision, and post-purchase behavior. The results show that the primary reason for purchasing fish fillets was to save cooking time (50%). Recommendations from family or friends were the main sources of information (34.55%), with product freshness being the most important information (80.91%). Product quality was the main consideration in evaluating alternatives (30%), and the majority of consumers (38.18%) compared products before purchasing. Supermarkets were the preferred place of purchase (56.36%), and product quality was the most influential factor in the final decision (29.09%). After purchasing, most consumers were satisfied (53.64%), intended to repurchase (51.82%), and had recommended the product to others (58.18%). The study concludes that practicality and product quality are the key factors influencing consumer decisions, and should be prioritized in fish fillet marketing strategies.